A Nanoparticle-Conjugated Anti-TBK1 siRNA Induces Autophagy-Related Apoptosis and Enhances cGAS-STING Pathway in GBM Cells. (11th December 2021) - Xu, Shengchao; Yan, Xi; Tang, Lu; Dai, Gan; Luo, Chengke
Abstract : Background . Gene therapy shows considerable clinical benefit in cancer therapy, in which single-stranded ribonucleic acid (siRNA) is a promising strategy in the treatment of glioblastoma (GBM). TANK-binding kinase 1 (TBK1) is critical in tumorigenesis and development, which lays a foundation for an ideal target for tumor therapy. However, the practical application of free siRNA is limited. It is urgent to develop novel strategies to deliver TBK1 siRNA to activate apoptosis and cGAS-STING pathway as a therapeutic strategy for GBM. Methods . The expression and prognostic value of TBK1 were evaluated in the TCGA, CGGA, and GTEx databases. A novel gene delivery system was designed here via PEGylated reduced graphene oxide (rGO-PEG) to targeted delivery of anti-TBK1 siRNA efficiently. The efficacy of TBK1si/rGO-PEG was evaluated in GBM cells. The underlying pathways were explored by Western blot. Results . TBK1 was highly expressed in glioma samples, and its high expression indicated poor prognoses in glioma patients. The rGO-PEG presented great efficiency in targeted delivery of TBK1si RNA into GBM cells with up to 97.1% transfection efficiency. TBK1si/rGO-PEG exhibited anti-GBM activities by inhibiting TBK1 and autophagy, as well as activating apoptosis and cGAS-STING pathway. Conclusion . The rGO-PEG could be an efficient system facilitating the delivery of specific siRNA. TBK1si/rGO-PEG could be a novel strategy for the treatment of GBM.